2015
DOI: 10.2147/dddt.s75752
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy in combination with chemoradiotherapy in the treatment of oral carcinomas in advanced stages of disease: efficacy, safety, and clinical outcomes in a small number of selected cases

Abstract: IntroductionElectrochemotherapy (ECT) is a new therapeutic method that is used in oncology as palliative treatment in patients with recurrent head and neck tumors and who are not candidates for standard therapeutic options. The aim of our study was to evaluate the cytoreductive effect of ECT in patients subjected to chemoradiotherapy for squamous cell carcinoma of the oral cavity. The primary endpoint of the study was to verify tumor debulking after ECT treatment as neoadjuvant, before conventional chemoradiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“… Landstorm FJ et al, Acta Otolaryngol, 2015 [ 33 ] Prospective 18 Nd (100) Median 58 months BLM i.t. Domanico R et al, Drug Des Devel Ther, 2015 [ 34 ] Experimental 4 0 3 (75) 3 (75) 1 BLM i.v. Campana LG et al, EJSO, 2016 [ 18 ] Prospective multicenter 35 14 (40.7%) 21 (60) 30 (85.2) 1–12 (evaluation at 2 months) BLM i.v.&i.t., CDDP i.t.…”
Section: Discussionmentioning
confidence: 99%
“… Landstorm FJ et al, Acta Otolaryngol, 2015 [ 33 ] Prospective 18 Nd (100) Median 58 months BLM i.t. Domanico R et al, Drug Des Devel Ther, 2015 [ 34 ] Experimental 4 0 3 (75) 3 (75) 1 BLM i.v. Campana LG et al, EJSO, 2016 [ 18 ] Prospective multicenter 35 14 (40.7%) 21 (60) 30 (85.2) 1–12 (evaluation at 2 months) BLM i.v.&i.t., CDDP i.t.…”
Section: Discussionmentioning
confidence: 99%
“…Most publications reported on studies of prospective design, i.e., phase 2 observational studies [17][18][19][20]22,[24][25][26][27][29][30][31][33][34][35]; only three studies were retrospective [25][26][27], and one was a case report [36] (Table 1). Four studies were reported in more than one publication [15][16][17]21,23,25,28,29,32,33].…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…Four studies were reported in more than one publication [15][16][17]21,23,25,28,29,32,33]. Individual patient data were reported in 10 studies (86 patients, 52.4%) [17,18,20,[24][25][26]29,33,34,36] and group data in six studies (78 patients, 47.6%) [19,22,27,30,31,35]. The number of patients with mucosal HNC treated in these studies ranged from 1 to 43 patients (median 6.5; interquartile range 2.5-15.5).…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…In contrast to radiotherapy, it is possible to repeat several ECT cycles without precluding other types of treatment on the same patient if new metastases develop. ECT has a favorable cost-effectiveness ratio with a cost of € 1,901.05 per achieved response in comparison with other techniques to control and treat cutaneous and subcutaneous melanomas [13, 19, 24, 33, 34].…”
Section: Advantage and Disadvantage Of Ectmentioning
confidence: 99%
“…It is applied for treating melanomas, sarcomas, and other types of skin cancer, cervix leiomyosarcoma, and breast cancer. Figure 1 shows the result of an actual treatment using ECT [2, 13–15].…”
Section: Introductionmentioning
confidence: 99%